Studies in Co(II) Cu(II) and Ni(II) and Complexes with Substituted Pyrazoline and Pyrazole at 0.1 Ionic Strength pH-metrically - Kadu, M.V.; Jamode, V.S.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
The interaction of Co(II), Cu(II) and Ni(II) with 3-(2-hydroxy- 5-methyl phenyl)-4-benzoyl-5-phenyl-1-pyridoyl-Δ2 -pyrazoline and 3-(2-hydroxy-3-bromo-5-methyl phenyl)-4-benzoyl-5-(4-methoxy phenyl)-1-pyridoyl pyrazole have been investigated by Bjerrum method as adopted by Calvin and Wilson. The stability constants of I : I and I : 2 complexes of Co(II), Cu(II) and Ni(II) have been studied at constant temperature (27 ± 0.1ºC) and 0.1 M ionic strength (NaOH) in 70% DMF-water mixture. It is observed that formation of 1 : 1 and 1 : 2 complexes is occurring simultaneously.